NCDs AND QUALITY OF LIFE OF UNIVERSITY PROFESSORS (Fiep Bulletin - online, 2019)
The quality of life of the university professor is being sought, for this reason, is imperative to research, to understand and toobtain positive results, both in the personal aspect and in the teaching and learning process of the students, considering the growth ofinstitutions in the current context. Regard this aspect, an important issue that emerges is that concerning chronic diseases (NCDs) isnoncommunicable, the disease can disrupt or incapacitate a professional. The objective of this study was to detect and describe therelationship between teacher quality of life and nontransmissible chronic diseases. For this, a systematic review was used,considering articles presenting as clinical trials methodology and/or observational studies. Taking into account all the parametersevaluated in the four articles, it is possible to observe that the quality of life of university professors is deficient because it presents asignificant high percentual of physical inactivity, in a direct increase with the great propensity to develop NCDs
Keywords: university professors; quality of life; noncommunicable chronic diseases